2017
DOI: 10.1002/chem.201702989
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Magnetic Relaxation Pathways and Dual‐Emission Modulated by a Heterometallic Tb‐Pt Bonding Environment

Abstract: A heterometallic Tb-Pt complex, [Tb Pt (SAc) (H O) ] (SAc=thioacetate), was synthesized. Dual emission was modulated by the presence of a heterometallic Tb-Pt bonding environment. The heterometallic Tb-Pt bond lowers the symmetry of the Tb ion and enhanced the emission efficiency. In addition, the Tb-Pt complex shows field-induced multiple magnetic relaxation pathways. Furthermore, it served as an antenna for the observed dual emission. In other words, the heterometallic Tb-Pt bond has a significant effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
(25 reference statements)
2
17
3
Order By: Relevance
“…In another example, polymorph‐specific J ‐splitting of the 5 D 0 → 7 F 2 Eu 3+ transition was observed in [Eu(pip) 3 (phen)] when compared to lanthanum‐doped europium compounds . Furthermore, emission intensity enhancement was induced by symmetry lowering in heterometallic Tb−Pt complex ([Tb 2 Pt 3 (SAc) 12 (H 2 O) 2 ]) . In contrast to these studies, the here observed polymorph‐specific spectral features of 1 – 3 cannot be ascribed to the introduction of guest ions or external forces, thus their origin must be related to the complexes’ intrinsic crystal structures.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…In another example, polymorph‐specific J ‐splitting of the 5 D 0 → 7 F 2 Eu 3+ transition was observed in [Eu(pip) 3 (phen)] when compared to lanthanum‐doped europium compounds . Furthermore, emission intensity enhancement was induced by symmetry lowering in heterometallic Tb−Pt complex ([Tb 2 Pt 3 (SAc) 12 (H 2 O) 2 ]) . In contrast to these studies, the here observed polymorph‐specific spectral features of 1 – 3 cannot be ascribed to the introduction of guest ions or external forces, thus their origin must be related to the complexes’ intrinsic crystal structures.…”
Section: Resultscontrasting
confidence: 83%
“…[67] Furthermore,e mission intensity enhancement was induced by symmetry lowering in heterometallic TbÀPt complex ([Tb 2 Pt 3 (SAc) 12 (H 2 O) 2 ]). [68] In contrast to these studies, the here observed polymorph-specific spectralf eatureso f1-3 cannot be ascribed to the introduction of guest ions or external forces, thus their origin must be related to the complexes' intrinsic crystal structures. Complexes 3a and 3c crystallize in the triclinic crystal system,s pace group P1.I nc ontrast, platelike 3b belongs to the monoclinic crystal system,s pace group P21/n (note:h eterometallic and homometallic complexes behavei dentically).…”
Section: Opticalproperties:e Mission Spectroscopycontrasting
confidence: 73%
“…For example, one maximum may originate from the relaxation pathway of the first kind of magnetic ions in the SMM compound while two others result from another kind of magnetic ion. In fact, these three maxima in χ were also recently observed in some polynuclear systems [63][64][65].…”
Section: Discussionsupporting
confidence: 66%
“…Lanthanoid (Ln) ions have become prime candidates for SMMs owing to their high spin states, large spin‐orbit couplings, and large anisotropies resulting from quadrupole moments, giving the Ln ions oblate, prolate, and spherical electron density distributions . Mono‐ to poly‐nuclear clusters involving d‐ and f‐block metal ions have been used with series of ligands to design SMMs ,. Most molecular design strategies focus on maximizing the total spin quantum number through molecular clusters by using exchange couplings to increase the effective Δ ( Δ eff ) .…”
Section: Introductionmentioning
confidence: 99%